A percepção da liderança no clima organizacional: um estudo de caso na Somave Alimentos - Santos, Camila Schwartzhaupt (2023)
This article seeks to understand the perception of leadership in the organizational climate in the company Somave Alimentos located in the city of Passo Fundo, Rio Grande do Sul. This theme has been much commented on and studied since the past, as it reflects on the company's environment and on leadership in general. The general objective of this research was to understand the perception of leadership in the organizational climate and how it can impact the other sectors of the company. The theoretical framework used in the research brings concepts about leadership, leadership styles, organizational climate, measurement models and dimensions of analysis. The research is characterized as a diagnostic research with a quantitative approach, carried out through Google Forms with the participation of 17 workers from the cutting sector, where it is possible to understand the vision of leadership and the organizational climate in the company. In view of this, it is highlighted how important it is to have a structured and effective leadership, which reflects on the quality of the organizational climate.